Estudo do processo de extração do óleo da semente de Moringa oleifera Lam. visando a produção de biodiesel - Almeida, Naiara Campos de (2015)
The Moringa oleifera Lamarck is a woody plant that grows quickly and adapts well to poor soil conditions, requiring no special care. Being an inedible raw material, with high oil content, has been considered a promising raw material to production biodiesel. This work aimed to study the conventional extraction processes (Soxhlet and press) and unconventional (ultrasound) in order to improve the methods to obtain the largest amount of oil, with physicochemical characteristics ideal to biodiesel production. The moringa seed from the Experimental Farm of UEM was first physical and chemical characterized. The physical characterization was performed by determining the roundness, bulk density and angle of repose. The chemical characterization followed the methodology proposed by the Official Methods of Analysis (AOAC, 2000), in which it was determined the moisture content, ash, lipids, protein, fiber gravel and total carbohydrates. The seed had a high oil content (36.28 %) and protein (33.03 %) and low humidity (7.11 %). Next, were studied the drying process of Moringa seeds at temperatures of 40, 50, 60, 70 and 80°C with constant air speed of 1.5 m/s. The rise in temperature increased the rate of drying and the effective diffusivity, which ranged from 0.79x10-10 to 2.14x10-10 m/s² and the activation energy was 24.33 kJ/mol. The best fit to drying temperature of 40°C was the Logarithmic model and temperatures of 50, 60, 70 and 80°C was the diffusion approach. It was examined whether the drying process influenced the seed moringa oil extraction, when compared to the seed in nature. To the Soxhlet extraction the seeds in nature had a higher oil content compared to seeds to dry. In contrast, for extraction by ultrasound and press, both dry seeds as seeds in natura showed oil levels statistically equal. To the Soxhlet extraction was assessed the influence of the solvent (acetone, ethanol, petroleum ether, isopropanol and hexane) and extraction time (2, 4, 6 and 8 h) obtained in oil content, and the hexane solvent presented greater selectivity and showed the highest oil content (47.05 %). The pressing extraction was evaluated by the influence of pressure (8, 11 and 14 ton/cm²) and time such that the higher oil content (25.60 %) was obtained for 14 ton/cm² and 4 hours of extraction. To the extraction was carried out with ultrasound 2³ DCCR experimental design for the solvents hexane, petroleum ether and acetone, were evaluated for the extraction temperature parameters (25, 35 and 45°C), residence time (30, 45 and 60 min) and seed mixture ratio: solvent (1:6, 1:8 and 1:10). The hexane solvent showed the most selectivity, such that obtained extracted oil 39.02 %, using a temperature of 25°C, time 60 min and mixture ratio of 1:10. Finally, the characterization of the oil was determined by saponification and acid values, moisture content, density and viscosity, and the composition of free fatty acids present therein. The results revealed that the crop showed high concentration of oleic acid (~ 76 %) and low acid value (0.89 to 1.57 kg KOH/mg) showing a favorable oil for biofuel production.